Determinants of Effective Information Technology Governance. (1st August 2012) - Ferguson, Colin; Green, Peter; Vaswani, Ravi; Wu, Gang (Henry)
<x xml:space="preserve">Abstract</x> This study examines relations between the overall level of effective information technology (IT) governance and five commonly advocated individual mechanisms of IT governance. It extends the examination of individual IT governance mechanisms to include a wider number of mechanisms, justifies the mechanisms investigated via agency theory, seeks to relate these mechanisms specifically to a perceived overall level of effective IT governance in organizations, and attempts to mitigate the problems of limited generalizability and selection bias by employing a survey and generalized sampling research methodology. The results from a survey of professional auditors reveal significant positive relations between the overall level of effective IT governance and three IT governance mechanisms: IT steering committees, senior management involvement in IT, and corporate performance measurement systems. Ex‐post sensitivity analyses reveal that the primary findings are qualitatively similar across internal auditors and external auditors, as well as information systems auditors (IS) and non‐IS auditors.